[Page 000-000a] - Reilly, William Edward, 1827-1886 (My University, 1845)
Cadet at the Royal Military Academy, Woolich at age fifteen and commissioned second lieuenant in the Royal Artillery 1854. Served in Crimea, awarded the Legion d'Honneur. Became a regimental colonel in 1877, commander of the Royal Artillery, Aldershot in 1879, director of artillery at the War Office, 1883 and inspector-general of artillery in 1885. He attained the rank of major-general before he died.
Course of practical artillery
Fair copy manuscript, 4to, half straight grain moroccon and embossed cloth sides. Gold tooling on spine and title in gold, on spine and front cover. Although the watermarks are from 1845 and that is the date on the spine, the maturity of the handwriting and the quality of the illustrations suggest that the author was an older man when this work was completed. Reilly published several works on military and artillery topics but this manuscript remains unpublished. It may have been a course of lectures delivered to the academy but the presence of a decorated title page and table of contents suggest it was a work prepared for publication. Illustrations : title page, table of contents, 2 line drawings, 42 pages of painted illustrations, 5 pullout pages with illustrations, one of which is painted, two diagrams, 15 tables.
Keywords: Artillery -- Handbooks, manuals, etc.; Artillery drill and tactics -- History -- 19th century; Artillery ?- Ireland; Artillery -- Study and teaching